Investigation of the stability of cerium oxide in diesel fuel for nano-enhanced fuel formulation - Saleem, Ali Ba; R., Mamat; Hagos, F. Y.; Abdul Adam, Abdullah; A., Arman (2021)
Abstract. Enhancing fuels through nano-addition has become a prospect in keeping both renewable and non-renewable fuels as energy sources for the transportation sector. One of the challenges when using nanofluids in a specific system is the fluid’s ability to be stable for a longer period. Undesired settlement of nanoparticles can cause damage to the system operating within its limits due to contamination, therefore stability study has paramount importance in the nano-enhanced fuel introduction in internal combustion engines. checking nanofluid stabilization consider a challenge since it takes time and it has tendency to aggregate in certain time, therefore UV vis device was a perfect tool to investigate the stability of the nano fuel. Three-step method using UV-Vis spectral absorbency device was selected to measure the nanofluid and ensure the stability of the solution daily. Cerium oxides consider one of the challenging nano additives to blend with fuel. To measure its stability, it was observed that when the nanofluid fuel was mixed with nanoparticles in quantities estimated at 25, 50, and 75 ppm, the nano fuel solution showed a high stability capacity in the first days, which indicate revealed that blending at high speeds followed by ultrasonication in an ultrasonic homogenizer for 40 minutes increases the stability of the mixes. The nano fluid fuel was gradually decreasing during the next following 8 days, but all of the blended fuel remains stable for percentage above 80 percent that UV-Vis 3 step method is trustable for investigating the stability of the nano enhanced fuel.